2023
DOI: 10.3390/phycology3010009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on the Growth of Holopelagic Sargassum Species

Abstract: Holopelagic Sargassum species have bloomed recurrently in the northern tropical Atlantic since 2011, causing socioeconomic and environmental problems. Little is known about their basic biology and responses to the abiotic environment. The aim of this study was to determine how temperature affects the growth rates of the genotypes S. fluitans III, S. natans I, and S. natans VIII that predominate in these blooms. The growth rates were evaluated in specially designed ex situ systems between 22 and 31 °C, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…In situ observations have also revealed that three different morphotypes are involved in the proliferation ( Sargassum fluitans III, Sargassum natans I, and Sargassum natans VIII e.g., Alleyne et al., 2023; Dibner et al., 2022; García‐Sánchez et al., 2020; Schell et al., 2015). The eco‐physiological features are species dependent, and it has been shown that Sargassum fluitans III, which has been the dominant morphotype over the recent years (García‐Sánchez et al., 2020), grows significantly faster than the Sargassum natans morphotypes (Changeux et al., 2023; Corbin & Oxenford, 2023; Magaña‐Gallegos et al., 2023a, 2023b). However there is no convergence of the recent studies on the temperature dependance of the different morphotypes (Corbin & Oxenford, 2023; Magaña‐Gallegos et al., 2023a, 2023b) and there is no knowledge of the salinity, light, or senescence dependence of the different morphotypes.…”
Section: Materials and Methods: The Forecasting Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…In situ observations have also revealed that three different morphotypes are involved in the proliferation ( Sargassum fluitans III, Sargassum natans I, and Sargassum natans VIII e.g., Alleyne et al., 2023; Dibner et al., 2022; García‐Sánchez et al., 2020; Schell et al., 2015). The eco‐physiological features are species dependent, and it has been shown that Sargassum fluitans III, which has been the dominant morphotype over the recent years (García‐Sánchez et al., 2020), grows significantly faster than the Sargassum natans morphotypes (Changeux et al., 2023; Corbin & Oxenford, 2023; Magaña‐Gallegos et al., 2023a, 2023b). However there is no convergence of the recent studies on the temperature dependance of the different morphotypes (Corbin & Oxenford, 2023; Magaña‐Gallegos et al., 2023a, 2023b) and there is no knowledge of the salinity, light, or senescence dependence of the different morphotypes.…”
Section: Materials and Methods: The Forecasting Strategymentioning
confidence: 99%
“…The modeling of growth and mortality characteristics is poorly constrained by observations or experiments, so this aspect is particularly challenging. The main factors that were identified as essential to take into account to represent Sargassum growth are internal nutrient reserves of nitrogen and phosphorus (Hanisak, 1983), dissolved inorganic nutrients (nitrate, phosphate, ammonium) in the external medium (Changeux et al, 2023;Lapointe, 1986Lapointe, , 1995Lapointe et al, 2014Lapointe et al, , 2021Magaña-Gallegos et al, 2023a, 2023b, solar radiation (Hanisak & Samuel, 1987;Lapointe, 1995), sea surface temperature (Hanisak & Samuel, 1987;Magaña-Gallegos et al, 2023b), sea surface salinity (Hanisak & Samuel, 1987), and surface wind speed (Magaña-Gallegos et al (2023a) found that continuous movement of Sargassum is required to allow growth in ex-situ culture systems).…”
Section: Materials and Methods: The Forecasting Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in regional biogeochemistry, natural modes of climate variability and the intensity of Atlantic hurricane seasons may ultimately be related to anthropogenic climate change. Longer term, climate models predict substantial warming of the surface tropical Atlantic over 2005-50, in the range 1.0 °C-1.5 °C [27], in a region where sargassum is currently growing at close to optimum summer temperatures [28]. Associated ongoing changes in regional biogeochemistry, modes of variability and hurricane seasons are highly uncertain, with the effect of these on future sargassum abundance and distribution unclear.…”
Section: Introductionmentioning
confidence: 99%
“…( S. natans I and S. fluitans ) have found that light has a strong influence on their growth rates, similar to the effects of temperature (Hanisak & Samuel 1987; Magaña‐Gallegos et al . 2023). Light requirements of holopelagic Sargassum species are much higher than those of benthic species, obscuring differences between the former.…”
Section: Introductionmentioning
confidence: 99%